Association between healthy food environment and metabolic syndrome, waist circumference, and systolic blood pressure in older adults in Southern Brazil - Souza, Bianca Bittencourt de; Quialheiro, Anna; Correa, Elizabeth Nappi; Rech, Cassiano Ricardo; Giehl, Maruí Weber Corseuil; d’Orsi, Eleonora (Frontiers in Aging, 2022)
The aim of this study was to investigate the association between healthy food outlet proximity, metabolic syndrome (MS), and two of its components, waist circumference (WC) and systolic blood pressure (SBP), in older adults (63–107 years old, median age 73 years) living in Florianópolis, South Brazil in 2013–2014. This is a cross-sectional analysis of the second wave of the EpiFloripa Aging Cohort Study. Individual-level data on MS, WC, SBP, and socio-demographic and health-related characteristics were collected from face to face interviews. The healthy food environment was assessed via the number and types of establishments present. The residences of older adult participants were georeferenced using Geographical Information System (GIS) software. The number of each type of food establishment in a 500 m buffer around the each residence was determined. Multivariate linear regression was used to test association between food outlet proximity and continuous outcomes (SBP and WC), and multiple logistic regression was used to examine the relations between the predictor variables and the dichotomous outcome of MS (yes/no). The study revealed that greater frequency of supermarkets and restaurants in the neighborhood was associated with a lower likelihood of having MS. WC was lower in individuals living in places with greater availability of greengrocers’ shops and restaurants. The results demonstrated that the number of establishments in a neighborhood is associated with cardiometabolic outcomes, and the likelihood of MS and increased WC is lower for older adults who live in neighborhoods with more access to establishments that sell foundational components of a healthy diet.